Influence of the processing temperature on the tribological and mechanical properties of poly-ether-ether-ketone (PEEK) polymer. (February 2016) - Zalaznik, M.; Kalin, M.; Novak, S.
Abstract: The main aim of this research was to investigate the influence of different processing temperatures on the properties of pure poly-ether-ether-ketone (PEEK). In order to do this, we used a variation of compression moulding, which enabled us to use different processing temperatures, including temperatures below the melting point of PEEK. The PEEK samples were produced at temperatures below, around and above the melting point of PEEK and were compared to a commercially available PEEK material produced with a conventional procedure. The results of the dry-sliding tribological tests, the hardness measurements and the XRD analyses show that the processing temperature greatly influences the hardness and the crystallinity, which in turn affects the tribological behaviour. Highlights: A non-conventional technique enabled the use of different processing temperatures. The material properties were greatly affected by the processing temperatures. Higher processing temperatures led to higher hardness and wear but lower friction. The required PEEK properties were reached at temperatures below melting point.